Creative intelligence and thinking styles - López Martínez, Olivia; Martín Brufau, Ramón (Anales de Psicología / Annals of Psychology, 2010)
The thinking styles (legislative, ejcutive and judicial styles) and creativity had been put in relation in the Sternberg’s theory of Mental Self-Government. The general objective of this work is to explore the relation-ship between thinking styles and creativity in students of the faculty of Psychology and Education. The Sternberg-Wagner Thinking Styles Inven-tory and the test of Corbalán (CREA) were administrated in a sample composed by 237 students. The research was conducted with a mean difference analisys between the most creative subjects (using one standard deviation over the mean as the cutpoint to identify the most creative subjects) and the medium and low creativity persons. Mean differences in the use of the legislative style between the high creative students and the rest were founded. This results indicate that the high creativity students prefer the legislative styles. The data founded here suggests that the CREA seems to be a good instrument to discriminate those subjects with high creativity capacities.